2016
DOI: 10.1037/a0039979
|View full text |Cite
|
Sign up to set email alerts
|

An integrated utility-based model of conflict evaluation and resolution in the Stroop task.

Abstract: Cognitive control allows humans to direct and coordinate their thoughts and actions in a flexible way, in order to reach internal goals regardless of interference and distraction. The hallmark test used to examine cognitive control is the Stroop task, which elicits both the weakly learned but goal-relevant and the strongly learned but goal-irrelevant response tendencies, and requires people to follow the former while ignoring the latter. After reviewing the existing computational models of cognitive control in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 135 publications
(380 reference statements)
1
16
0
Order By: Relevance
“…In order to separately predict reaction times on correct trials and accuracies we fitted Chuderski & Smolen, 2016;Heathcote et al, 1991;MacLeod, 1991) for the reaction times, and for accuracy 2 (intercept: M = 2.5; SD = 3;…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In order to separately predict reaction times on correct trials and accuracies we fitted Chuderski & Smolen, 2016;Heathcote et al, 1991;MacLeod, 1991) for the reaction times, and for accuracy 2 (intercept: M = 2.5; SD = 3;…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The descriptions of BTP include some clear references to intellectual ability and imply that cognitive resources might be necessary to use temporal perspectives effectively. Cognitive flexibility enables individuals to achieve their goals and override automatic processes and is usually regarded as a component of executive functioning (also referred to as executive control ; Miyake et al, 2000; Diamond, 2013; Chuderski and Smolen, 2016). Recent studies have shown that two types of executive function appear to be relevant to personality, namely working memory capacity and response inhibition (Hofmann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In order to go beyond empirical data and to understand the cognitive processes fully it is important to test mechanistic process models that try to explicitly state the underlying neurocognitive mechanisms (cf. Wichary et al, 2015b; Chuderski and Smolen, 2016). Within the domain of strategy selection in multi-attribute choice, there exists an empirical challenge described by Newell (2005) that it is impossible to distinguish, based on behavior, the accuracy of the unified and multiple strategy models described in the previous section.…”
Section: Toward a Neurocognitive Model Of Decision Strategy Selectionmentioning
confidence: 99%